When attending the World's Fair, visit beautiful Sea Cliff 250 ft. altitude : No mosquitos. - DeNoon, Christopher ([New York] : WPA Federal Art Project, Dis. 4, 1938)
Poster promoting Sea Cliff, Long Island for tourism, showing seacoast with cliffs, road, and New York World's Fair buildings.